Phenolic Contents of Romanian Wines with Different Geographical Origins - Geana, Elisabeta-Irina; Elena Ionete, Roxana; Tudorache, Aurelia; Pasa, Rodica; Postolache, Elena; Ranca, Aurora (Asian Journal of Chemistry, 2011)
Phenolic compounds in wine are important because they contribute to the colour, taste and body of the wine. The skin and seeds of the grape berry are rich in phenolic compounds. Some have strong antioxidant and anticancer activities and they are routinely consumed in the human diet in significant quantities. Wines from four different Romanian grape cultivars were analyzed in order to determine their phenolic contents. For the analysis, reversed phase-high performance liquid chromatography (RP-HPLC) coupled with diode array detection was used. The most abundant phenolic substance detected was (+)-catechin and (-)-epicatechin as flavonoid and gallic acid as a phenolic acid. As a result, it was determined that types and concentrations of phenolics changed according to the wines from different cultivars.